Meaningful games : exploring language with game theory - Clark, Robin Lee, 1957- (MIT Press, 2012)
In this work, Robin Clark explains in an accessible manner the usefulness of game theory in thinking about a wide range of issues in linguistics. Clark argues that we use grammar strategically to signal our intended meanings: our choices as speaker are conditioned by what choices the hearer will make interpreting what we say.